2020
DOI: 10.1242/jeb.215905
|View full text |Cite
|
Sign up to set email alerts
|

The brains of six African mole-rat species show divergent responses to hypoxia

Abstract: Mole-rats are champions of self-preservation, with increased longevity compared with other rodents their size, strong antioxidant capabilities and specialized defenses against endogenous oxidative stress. However, how the brains of these subterranean mammals handle acute in vivo hypoxia is poorly understood. This study is the first to examine the molecular response to low oxygen in six different species of hypoxia-tolerant mole-rats from sub-Saharan Africa. Protein carbonylation, a known marker of DNA damage (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 68 publications
1
43
1
Order By: Relevance
“…MiR-31 and miR-153 antagonistically regulate the HIF pathway: miR-31 promotes its activation via the ablation of the HIF repressor, whereas miR-153 directly binds to the HIF-1α 3′-UTR and inhibits HIF-1α translation (Liu et al, 2010). This interaction demonstrates , anoxic freshwater crayfish (English et al, 2018) and hypoxic high-altitude Tibetan pigs (Zhang et al, 2015), and is down-regulated in hypoxic subterranean naked mole rats (Logan et al, 2020).…”
Section: The Role Of Oxymirs In Hypoxic Estuarine Habitats Sea Cucumbersmentioning
confidence: 81%
See 3 more Smart Citations
“…MiR-31 and miR-153 antagonistically regulate the HIF pathway: miR-31 promotes its activation via the ablation of the HIF repressor, whereas miR-153 directly binds to the HIF-1α 3′-UTR and inhibits HIF-1α translation (Liu et al, 2010). This interaction demonstrates , anoxic freshwater crayfish (English et al, 2018) and hypoxic high-altitude Tibetan pigs (Zhang et al, 2015), and is down-regulated in hypoxic subterranean naked mole rats (Logan et al, 2020).…”
Section: The Role Of Oxymirs In Hypoxic Estuarine Habitats Sea Cucumbersmentioning
confidence: 81%
“…To explore the role of OxymiRs in naked mole rat neuroprotection, an international team of researchers examined a group of 27 hypoxia-associated miRNAs (Logan et al, 2020). Their results present miRNAs as modulators of neuroprotection in hypoxic mole rats; induction of hypoxia revealed that a subset of miRNAs are involved in inhibiting apoptosis and neuroinflammatory regulation (Logan et al, 2020) (Fig. 4).…”
Section: Involvement Of Oxymirs In Hypoxic Subterranean Environments mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, some diving mammals experience dramatic hypoxemia (Meir et al, 2009) and I/R events (Zapol et al, 1979) during their repeated long-duration breath-holds and do not develop injuries from this lifestyle. Species that have adapted to live at high altitude or under other hypoxic conditions (e.g., burrowing) also avoid pathologies associated with exposure to chronic hypoxia (Logan et al, 2020). These natural models offer unique insights into the adaptive mechanisms underlying tolerance to hypoxia and/or I/R injury.…”
Section: Evolutionary Insights From Hypoxia-adapted Populationsmentioning
confidence: 99%